The Antibacterial Activity Test of Methanol and N-Hexane Fractions of Yellow Pumpkin Fruit Extract (Cucurbita moschata Duch) Against Escherichia coli and Staphylococcus aureus - Suleman, Abdul Wahid; Saparuddin Latu; Sriyanty Sadsyam; Safaruddin; Pradila (Universitas Muhammadiyah Klaten, 2025)
Infectious diseases are still a major health problem in several countries, especially in developing countries. The medication used to treat bacterial infections is obtained by utilizing herbal plants obtained from natural ingredients. Pumpkin fruit extract (Cucurbita moschata) contains flavonoids. tannins, saponins, and alkaloids Pumpkin fruit is effective as an antidiabetic, an antihypertensive, an antitumor, an antibacterial, and an antioxidant. This study aims to determine the antibacterial activity of the methanol and n-hexane fractions of yellow pumpkin (Cucurbita moschata) fruit extract and at what concentration the methanol and n-hexane fractions of yellow pumpkin (Cucurbita moschata) fruit extract can have antibacterial activity against Escherichia coli and Staphylococcus aureus. This research uses laboratory-experimental research methods. Antibacterial testing in this research involved sterilization, making test solutions, and testing. The results of the antibacterial test on the inhibition zone of the methanol fraction of pumpkin fruit against Escherichia coli and Staphylococcus aureus bacteria at concentrations of 20%, 30%, and 40% were in the strong category, while the n-hexane fraction had an inhibition zone in the weak category for Escherichia coli and Staphylococcus aureus bacteria. Conclusion: The methanol and n-hexane fractions have antibacterial activity against Escherichia coli and Staphylococcus aureus, and the concentrations with antibacterial activity are 20%, 30%, and 40%.